Therapeutic Drug Monitoring of Antibiotics: Defining the Therapeutic Range. Issue 1 (February 2022) - Abdul–Aziz, Mohd H.; Brady, Kara; Cotta, Menino Osbert; Roberts, Jason A.
Abstract : Purpose: In the present narrative review, the authors aimed to discuss the relationship between the pharmacokinetic/pharmacodynamic (PK/PD) of antibiotics and clinical response (including efficacy and toxicity). In addition, this review describes how this relationship can be applied to define the therapeutic range of a particular antibiotic (or antibiotic class) for therapeutic drug monitoring (TDM). Methods: Relevant clinical studies that examined the relationship between PK/PD of antibiotics and clinical response (efficacy and response) were reviewed. The review (performed for studies published in English up to September 2021) assessed only commonly used antibiotics (or antibiotic classes), including aminoglycosides, beta-lactam antibiotics, daptomycin, fluoroquinolones, glycopeptides (teicoplanin and vancomycin), and linezolid. The best currently available evidence was used to define the therapeutic range for these antibiotics. Results: The therapeutic range associated with maximal clinical efficacy and minimal toxicity is available for commonly used antibiotics, and these values can be implemented when TDM for antibiotics is performed. Additional data are needed to clarify the relationship between PK/PD indices and the development of antibiotic resistance. Conclusions: TDM should only be regarded as a means to achieve the main goal of providing safe and effective antibiotic therapy for all patients. The next critical step is to define exposures that can prevent the development of antibiotic resistance and include these exposures as therapeutic drug monitoring targets.